Sarcomatous carcinoma in biliary system: A retrospective study. Issue 8 (February 2019) - Zhang, Ning; Li, Yatong; Zhao, Mengyun; Chang, Xiaoyan; Qu, Qiang; He, Xiaodong
Abstract : Abstract: Sarcomatous carcinoma in biliary system, including sarcomatous intrahepatic cholangiocarcinoma (SIC) and sarcomatous choledochal carcinoma (SCC), is extremely rare and malignant. This retrospective study included 5 patients with SIC and 4 patients with SCC. Their basic characteristics, preoperative lab tests, preoperative imaging features, perioperative status, and follow-up information have been collected and analyzed. Lesions at different locations induced various preoperative symptoms. The history of choledocholithiasis or hepatolithiasis was remarkable in patients with SIC. Cancer antigen 19-9 appeared to be a key factor for both SIC and SCC. However, preoperative lab tests or imaging features could not distinguish SIC from intrahepatic cholangiocarcinoma, or SCC from choledochal carcinoma. Surgical treatments for all 9 patients were successful. Efficacy of adjuvant chemotherapy was not ideal. The prognosis of sarcomatous biliary carcinoma was enormously poor. Sarcomatous carcinoma in biliary system is extremely rare and malignant. Chronic inflammation could be critical in the currently unknown occurrence mechanism. Further research is urgently needed to improve the prognosis.